Peninggalan Arkeologis di Kepulauan Bacan - Syahruddin Mansyur (Balai Arkeologi Maluku, 2007)
History of Sultanate of Bacan early from association group of traditional society is called boldan led by a kolano. In kronik Bacan mentioned by that center of governance initially reside in Makian island, residing in northside island Bacan. As one part of from Moluco Kie Raha, Sultanate of Bacan own important role in this region. This matter, pursuant to with refer toing result of research which have been in this area. Island of Makian and its surroundings as location of early center of governance of Moluco Boldan Kie-Besi (The early beginning of Sultanate of Bacan), known to own to omit Prehistoric archaeology. Omit other;dissimilar archaeology come from a period of Islam and Colonial influence. This article try to give picture of cultural history in region of Archipelago of Bacan of pursuant to with refer toing result of research which have been done.